Agaw-dilim, agaw-liwanag - Abreu, Lualhati Milan (Quezon City University of the Philippines Press, 2009)
A creative nonfiction autobiographical work on the communist underground.
"Gawad Likhaan, the UP centennial literary prize winner" on cover.
Keywords: Communist Party of the Philippines (1930- ) -- History; Communism -- Philippines -- History; Philippines -- Politics and government; Philippines -- Social conditions